Enhanced antitumor activity of cucurbitacin B combined with cerulenin in osteosarcoma (Bangladesh Journal of Pharmacology, 2015)
In the present study, the effect of cucurbitacin B and cerulenin combination on osteosarcoma was investigated to develop an effective treatment regimen. The IC50 values of cerulenin and cucurbitacin B combination in the proportion of 1:1, 1:2 and 2:1 were  3.5, 7.2 and 8.6 μg/mL, respectively. The combination index (CI) values of